Quality assessment of treated wastewater to be reused in agriculture - M.H. Rahimi; N. Kalantari; M. Sharifidoost; M. Kazemi (Global Journal of Environmental Science and Management)
In this study, the quality of a treated wastewater for agricultural and irrigation purposes was investigated. 39 quality parameters were investigated at the entrance of an effluent channel to the destination plain in monthly time intervals during a year. The aim of this study was drawing an analogy between analyses results and the latest standards in the world (nationwide and internationally), the agricultural and irrigation usage indexes and the Wilcox diagram. The results showed that some parameters such as turbidity, total suspended solids, electrical conductivity, sodium, detergents, total coliform and focal coliform, ammonium, residual sodium carbonate, the Kelly’s Ratio and the Wilcox diagram were exceeding the permissible limit and are not suitable for agriculture and irrigation. It was found that the aquifers in the study area were polluted by natural salinity and geogenic source. As a result, application of the treated wastewater from Qom for agriculture and irrigation purposes needs to be revised and monitored. An action plan is also needed to manage a huge source of water and to avoid further environmental and health risks.